2021
DOI: 10.21203/rs.3.rs-412750/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hidden Danger of COVID-19 Outbreak: Evaluation of Subclinical Myocardial Dysfunction in Patients with Mild Symptoms

Abstract: Background: The COVID 19 infection, which is caused by the novel coronavirus SARS-CoV-2, has rapidly emerged as a global public health issue. Cardiac complications secondary to this infection are common and associated with mortality. This study aimed to evaluate whether subclinical myocardial dysfunction using left ventricular global longitudinal strain (LVGLS) in non-hospitalized mildly symptomatic COVID-19 patients.Methods: In this cross-sectional, single-center study, data were collected from non-hospitaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Ikonomidis et al could show an improved aortic function in 60 individuals after bariatric surgery (Ikonomidis et al, 2007). Similarly, Gul et al observed an improvement of aortic stiffness 1 year after laparoscopic sleeve gastrectomy in 53 obese individuals (Gul et al, 2021). Also, Brinkley et al could demonstrate an improved aortic stiffness in elderly obese after moderate and intensive caloric restriction combined with aerobic exercise training, but not with aerobic exercise training alone (Brinkley et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…Ikonomidis et al could show an improved aortic function in 60 individuals after bariatric surgery (Ikonomidis et al, 2007). Similarly, Gul et al observed an improvement of aortic stiffness 1 year after laparoscopic sleeve gastrectomy in 53 obese individuals (Gul et al, 2021). Also, Brinkley et al could demonstrate an improved aortic stiffness in elderly obese after moderate and intensive caloric restriction combined with aerobic exercise training, but not with aerobic exercise training alone (Brinkley et al, 2021).…”
Section: Discussionmentioning
confidence: 98%